Electrochemical Oxidation of Resorcinol in Aqueous Medium Using Boron-Doped Diamond Anode: Reaction Kinetics and Process Optimization with Response Surface Methodology - Körbahti, Bahadır K.; Demirbüken, Pelin (Frontiers in Chemistry, 2017)
Electrochemical oxidation of resorcinol in aqueous medium using boron-doped diamond anode (BDD) was investigated in a batch electrochemical reactor in the presence of Na2SO4 supporting electrolyte. The effect of process parameters such as resorcinol concentration (100-500 g/L), current density (2-10 mA/cm2), Na2SO4 concentration (0-20 g/L) and reaction temperature (25-45oC) was analyzed on COD removal, mass transfer coefficient (km), J/Jolim values (), and energy consumption using response surface methodology (RSM). The optimum operating conditions were determined as 300 mg/L resorcinol concentration, 8 mA/cm2 current density, 12 g/L Na2SO4 concentration and 34oC reaction temperature. 100% resorcinol removal and 89% COD removal were obtained in 120 min reaction time at response surface optimized conditions. These results confirmed that the electrochemical mineralization of resorcinol was successfully accomplished using BDD anode depending on the process conditions, however the formation of intermediates and by-products were further oxidized at much lower rate. The reaction kinetics were evaluated at optimum conditions and the reaction order of electrochemical oxidation of resorcinol in aqueous medium using BDD anode was determined as 1 based on COD concentration with the activation energy of 5.32 kJ/mol that was supported a diffusion-controlled reaction.